Evaluasi Kinerja Guru SMP Negeri melalui Lingkungan Kerja, Motivasi Intrinsik, dan Komitmen di Tapian Nauli Kabupaten Tapanuli Tengah - Johannes Simanjuntak (Neolectura, 2021)
The purpose of this study was to determine and analyze the influence of the work environment, intrinsic motivation, and commitment of the teaching profession on the performance of teachers of State Junior High Schools in Tapian Nauli District, Central Tapanuli Regency. Hypothesis testing using the F test (simultaneous) and t- test (partial). The level of confidence used is 95%, then the significant level (?) = 0.05. The research method used is a survey method by taking a census of 68 respondents as a sample. The research sample used is to use a population study, where the entire study population becomes the research sample. The data analysis technique in this study used a linear regression equation model. The results of this study indicate that the work environment variable does not have a significant effect on teacher performance, while the intrinsic motivation and teacher commitment variables have a significant effect on teacher performance. The work environment, intrinsic motivation, and teacher commitment have a significant effect on teacher performance.